1985
DOI: 10.1111/j.1432-1033.1985.tb09009.x
|View full text |Cite
|
Sign up to set email alerts
|

Cholecalcin (a 9‐kDa cholecalciferol‐induced calcium‐binding protein) messenger RNA

Abstract: In view of the possible physiological importance of the 9-kDa cholecalcin (a 9000-Mr cholecalciferol-induced calcium-binding protein) in the intestinal transport of calcium in mammals, the gene expression of this protein has been analysed. Its regulation in the digestive tract of the growing rat by calcitriol (1,25-dihydroxycholecalciferol) was studied using a specific cloned [32P]cDNA to 9-kDa cholecalcin. Northern hybridisation studies show that the cDNA sequence hybridises to a single 500 -600-nucleotide s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(20 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Total RNAs were electrophoresed in 1.5% (wt/vol) agarose-formaldehyde gel and blotted on filters (21). Mouse CaBP9K mRNA was detected with a rat CaBP9K cDNA clone (15).Tag mRNA was detected with the StuI-BamHI fragment containing the coding region of the large T antigen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNAs were electrophoresed in 1.5% (wt/vol) agarose-formaldehyde gel and blotted on filters (21). Mouse CaBP9K mRNA was detected with a rat CaBP9K cDNA clone (15).Tag mRNA was detected with the StuI-BamHI fragment containing the coding region of the large T antigen.…”
Section: Methodsmentioning
confidence: 99%
“…CaBP9K is found in several rat tissues, such as enterocytes, myometrium, and epithelial alveolar cells of the lung (14)(15)(16)(17).The uterine CaBP9K gene is under the positive control of estradiol; the gene is silent in ovariectomized rodents (18,19) and strongly activated after estradiol treatment (20,21). CaBP9K is also expressed in the kidney of the mouse (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…In the intestine, vitamin D appears to be the primary regulator for the calbindin D-9k gene at the transcriptional level (22)(23)(24)(25). However, no regulation by vitamin D is exerted on the gene in the uterus, where it seems to be primarily under estrogen regulation (7,26).…”
mentioning
confidence: 99%
“…Calcium binding protein was shown to be induced in rat intestine by la,25(0H)2D3 (18). DeLuca and his colleagues (19) reported that four distinct mRNAs were significantly increased in rat intestine when la,25(0H)2D3 was applied to vitamin D-deficient animals: these were vitamin D-dependent calcium-binding protein, mitochondrial ATP synthetase, and cytochrome oxidase subunits I and III.…”
mentioning
confidence: 99%